Financial Performance Evaluation Of PT Bank Rakyat Indonesia TBK Using Financial Ratio Analysis For 2020-2024 - Suharini, Suharini; Hastasari, Ratih (Journal of Economics and Business (JECOMBI), 2025)
This study evaluates the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk (BRI) for the 2020-2024 period using a quantitative descriptive approach. Financial ratio analysis includes Earnings Per Share (EPS), Price-to-Earnings (P/E) Ratio, Return on Equity (ROE), Dividend Yield, and Dividend Payout Ratio, with data obtained from BRI's financial reports and other official sources. The results indicate a significant increase in EPS and ROE, reflecting improved profitability and equity management efficiency. The decrease in the P/E Ratio suggests BRI's shares have become more affordable, while the increase in Dividend Yield and Dividend Payout Ratio demonstrates the company’s commitment to shareholders. This research provides strategic insights for investors, managers, and policymakers in assessing BRI’s financial performance. The main conclusion highlights that BRI has maintained solid financial performance amidst global economic challenges, making it an attractive option for investors seeking stability and growth.